Analisis Wacana Pada Lirik Lagu “Life Goes On” Karya Boy Group BTS - Puteri, Fransisca Nirmala Gunawan (Jurnal Industri Kreatif dan Inovatif, 2023)
Korean Pop (Kpop) is a type of modern alternative music genre originating from South Korea. Kpop is actually aproduct of Hallyu (Korean wave) which is also integrated with other Hallyu products such as films, food, fashionand other Korean culture. Kpop culture actors are synonymous with a group of people formed in a group (boygroup or girl group) who sing while performing modern dance choreography. Beyond The Scene or BangtanSeonyeondan (BTS) is one of the boy groups that is very popular at the moment. This research analyzes thediscourse in one of the lyrics of the Boy Group BTS song, entitled "Life Goes On". Researchers use a semioticapproach, by conducting pre-proliferation and post-proliferation analysis of the text to see what elements makeup this song and the extent to which this song influences listeners. This research shows that the text in the song"Life Goes on" is a song that motivates listeners to continue living life even though it feels difficult in the era ofthe Covid-19 pandemic. The many figurative words as substitutes for meaning make this song play around withmore emotions and feelings, because the listeners experience the same condition.